2004
DOI: 10.1073/pnas.0308259100
|View full text |Cite
|
Sign up to set email alerts
|

Notch is required for long-term memory in Drosophila

Abstract: A role for Notch in the elaboration of existing neural processes is emerging that is distinct from the increasingly well understood function of this gene in binary cell-fate decisions. Several research groups, by using a variety of organisms, have shown that Notch is important in the development of neural ultrastructure. Simultaneously, Presenilin (Psn) was identified both as a key mediator of Notch signaling and as a site of genetic lesions that cause earlyonset Alzheimer's disease. Here we demonstrate that N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(111 citation statements)
references
References 42 publications
6
102
0
1
Order By: Relevance
“…3D and Supporting Materials and Methods). Presente et al (29) have also reported that CS males acquires LTM lasting at least 2 days after 5-h conditioning in a similar chamber (12 ϫ 75 mm). Taken together, our result indicates that per mutants are defective in the formation of LTM regardless of the size of conditioning chambers.…”
Section: Overexpression Of a Repressor Isoform Of Creb Dcreb2-b Blomentioning
confidence: 78%
“…3D and Supporting Materials and Methods). Presente et al (29) have also reported that CS males acquires LTM lasting at least 2 days after 5-h conditioning in a similar chamber (12 ϫ 75 mm). Taken together, our result indicates that per mutants are defective in the formation of LTM regardless of the size of conditioning chambers.…”
Section: Overexpression Of a Repressor Isoform Of Creb Dcreb2-b Blomentioning
confidence: 78%
“…Identification of such target genes could be approached by using bioinformatics and/or transcription profiling. Recent profiling studies have identified a number of putative Stat92E target genes in the Drosophila eye disk and hematopoietic system (40,41), some of which include Notch signaling pathway genes that have already been implicated in LTM (42,43). Another mode of action of JAK/STAT signaling in LTM could be through chromatin remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…The acute nature of this effect on cognition, the limited time frame in which inhibition of ␥-secretase is required, and the transgene-specific nature of these effects suggests ␤-amyloid contributes to the cognitive dysfunction in Tg2576 mice. In addition to effects on ␤-amyloid, GSI can affect other proteins, such as Notch (Selkoe, 2001;Presente et al, 2004) and DCC␣ (Parent et al, 2005), implicated in learning and memory. Indeed, loss of presenilin function, a component of ␥-secretase, has been shown to result in impaired memory and synaptic plasticity (Saura et al, 2004).…”
Section: Discussionmentioning
confidence: 99%